2021
DOI: 10.4171/dm/858
|View full text |Cite
|
Sign up to set email alerts
|

Universally defining finitely generated subrings of global fields

Abstract: It is shown that any finitely generated subring of a global field has a universal first-order definition in its fraction field. This covers Koenigsmann's result for the ring of integers and its subsequent extensions to rings of integers in number fields and rings of S-integers in global function fields of odd characteristic. In this article a proof is presented which is uniform in all global fields, including the characteristic two case, where the result is entirely novel. Furthermore, the proposed method resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…By [4, Corollary 4.12], we have ๐ท is definable by a positive-existential ๎ˆธ ring (๐พ)-formula with ๐‘š quantifiers, that is, a formula which is logically equivalent to โˆƒ๐‘Œ 1 , โ€ฆ , ๐‘Œ ๐‘š ๐œ“ for some ๎ˆธ ring (๐พ)formula ๐œ“ built up from atomic ๎ˆธ ring (๐พ)-formulae using only conjunctions and disjunctions (no negations). By [4,Remark 3.4], this implies ๐ท can be described as in (2) for certain ๐‘Ÿ and ๐‘“ 1 , โ€ฆ , ๐‘“ ๐‘Ÿ , where one may choose ๐‘Ÿ = 1 when ๐พ is not algebraically closed. โ–ก…”
Section: Existentially Definable Subsets Of Fields and Number Of Quan...mentioning
confidence: 99%
See 1 more Smart Citation
“…By [4, Corollary 4.12], we have ๐ท is definable by a positive-existential ๎ˆธ ring (๐พ)-formula with ๐‘š quantifiers, that is, a formula which is logically equivalent to โˆƒ๐‘Œ 1 , โ€ฆ , ๐‘Œ ๐‘š ๐œ“ for some ๎ˆธ ring (๐พ)formula ๐œ“ built up from atomic ๎ˆธ ring (๐พ)-formulae using only conjunctions and disjunctions (no negations). By [4,Remark 3.4], this implies ๐ท can be described as in (2) for certain ๐‘Ÿ and ๐‘“ 1 , โ€ฆ , ๐‘“ ๐‘Ÿ , where one may choose ๐‘Ÿ = 1 when ๐พ is not algebraically closed. โ–ก…”
Section: Existentially Definable Subsets Of Fields and Number Of Quan...mentioning
confidence: 99%
“…Consider ๐‘ฅ โˆˆ ๐”ช ๐‘ค for some ๐‘ค โˆˆ ๎‰‚ ๐พ โงต ๐‘†. As in the proof of [2, Lemma 6.6], we can find (๐‘Ž, ๐‘) โˆˆ ฮฆ ๐‘† ๐‘ข such that ฮ”[๐‘Ž2 , ๐‘๐œ‹) ๐พ = ๐‘† โˆช {๐‘ค} and ๐‘ค(1 + 4๐‘Ž 2 ) = 0. We must then have ๐‘ค(๐‘๐œ‹) is odd by Proposition 3.4, and since ๐‘ค(๐œ‹) is even, this implies ๐‘ค(๐‘) is odd.…”
mentioning
confidence: 99%
“…In [Koe16;Par13;EM18] the number of quantifiers was not counted; according to an older preprint of Koenigsmann, his technique leads to a universal defintion with 418 quantifiers [Koe10, Theorem 1]. In [Daa21] it was shown that rings of S-integers in global fields have a universal definition with 37 quantifiers; in the case of Z in Q, this was further refined by Sun and Zhang to 32 quantifiers in [ZS21].…”
Section: S-integers O S We Havementioning
confidence: 99%
“…Quaternion algebras (and quadratic forms) over global fields have played a historic role in establishing existential definability of subrings of global fields. Hence, in Section 3 we survey some algebraic ingredients regarding global fields and quaternion algebras -more details can be found in [Daa21,Sections 3 and 4].…”
Section: S-integers O S We Havementioning
confidence: 99%
See 1 more Smart Citation